Indikator Keuangan dalam Laporan Keuangan dan Kebijakan Dividen - Tang, Sukiantono; Elvin, Elvin (E-Jurnal Akuntansi; Vol 32 No 10 (2022), 2022)
This study aims to analyze the relationship between the financial indicators contained in the financial statements and dividend policy. Companies that are listed on the Indonesia Stock Exchange and meet the criteria set out in the study are used as research samples. This study uses 631 observational data from 2017 - 2021 obtained from the company's official website and the Indonesia Stock Exchange. Panel data regression is used to examine the effect of each variable on dividend policy. The best regression model in this study is the Fixed Effect Model. This study shows that free cash flow; firm risk; and return on equity have a significant positive effect on dividend policy. In addition; market to book value ratio and net asset growth have a significant negative effect. Other variables used in this study do not affect dividend policy. Keywords: Dividend Policy; Profitability; Liquidity; Financial Ratios.